Transversal competencies for employability: From higher education to the labour market - Belchior-Rocha, H. (2022)
Aligning learning goals with the needs of the labour market is a difficult task for universities, especially in the present day. Although organisations seek professionals with flexible and varied skills, universities often underestimate the importance of cross-curricular skills. Thus, this article aims to identify the perception of recent graduates as to the importance of the transversal skills that they acquired and developed at university and the ways in which they are now applied in the work environment. In this exploratory study, we sent a questionnaire to recent graduates that allowed us to analyse the development and applicability of these competencies in organisations. The results are further discussed within the broader framework of how universities adapt to the strong socio-economic challenges that characterise current times and the integration of recent graduates into the labour market.